Mapping of Farmer Economic Institutions for the Development of Food Crop Farmers Corporations in East Java - Gunawan; Ardiansyah; C Tafakresnanto; Evy Latifah (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
To increase the reinforcement of farmer capacity, farmer institutions and business capacity become the primary capital for forming farmer corporations. Hence, it is necessary to develop a mapping of agricultural areas based on farmer corporations, especially food commodities in East Java. It combines a series of programs, especially farmer corporations, into one unified whole to align with the Strategic Planning for Regional Development.  Mapping of farmer economic institutions (KEP) or farmer group classes to find out which farmer group classes have the potential to become farmer economic institutions. Middle and primary-class farmer groups are a class having the potential to be developed and included as a category of farmer economic institutions (KEP). Accordingly, agricultural areas, which are rice, maize, and soybean areas, can be delineated, having the potential to be developed as a farmer economic institution as a form of farmer corporation in the region. From the research results, it is obtained that farmer economic institutions (KEP) exist in several regencies in East Java. The highest economic institutions were formed in the regency of Tulungagung and Bojonegoro. Some regencies only have one institution that can be formed. The number of formed farmer economic institutions (KEP) can create farmer corporations which are essential for the growth and development of farmer corporations as a basis for improving farmer welfare.